Frameworks for innovation, collaboration, and change - Lages, Luis F. (2022)
The value creation wheel (VCW) is the decision-making meta-framework recommended to address innovation, collaboration, and change challenges in formal relationships. The VCW can integrate, complement, or be joined with other frameworks, tools, and theories to address the challenges of formal relationships. The VCW's ability to incorporate intra- and interorganizational insights emerging from internal and external stakeholders is especially useful in solving the challenges of collaborative arrangements. VCW solutions are often more realistic than Design Thinking, Creative Problem-Solving, and Lean because they accommodate the views of various stakeholders about ideas and filters, and because key decision makers must be involved in the main stages of the decision-making process.